Perencanaan Line Balaning Guna Meningkatkan Output Produksi - Teguh Baroto (Department Industrial Engineering, University of Muhammadiyah Malang, 2001)
Every companyw ill alwaysh avem aing oal in a maximumb ennefit.F or this, onef actorwhich support his is how to makea good productionp rocessT. his will be reachedif balancingline of productionfl oor hasa verages tressingo f work especiallyfo r assemblyc ompanyb ecausematerial handling in a work station will influence alother work station and cause production targetof companyw on't be available.For getting line balancing use Rank Positional Weighat (RPW), method which is aheuristicm ethodst hat is statemenot f trial and error approachingT.h is methodd ependso n thefunction value for each work operation based on the standard time for each work activitiesfollowingt hep roductionp rocessra nking( presedencdeia gram).From the analysis using RPW method can be found optimum balance delay to each typeof ARM producti s from 60,46% to 20,5488% with productiono utputl lom 113,50u nits/daybecome 116 unit/day, and also work efiiciency from 60,50 yo to 78,4511 o%, with workstationnumbera bout7 work stationsI.n otherh andf or type ofBED product1 5 hasb alanced elayf rom35,29o /oto 16,454w ith productiono utputi ncreaseft om 77,44m t/day become1 20u niVdaya ndalso hase fficiencya bout6 4,710 /ob ecome8 3,548% with work stationn umbera bout6 . Theni tcan be concludedt hat work stationd esignu sing RPW methodw ill increaseo utput produotespeciallfyo r assemblyc ompany.